PEWARISAN RUGAE PALATINA ORANGTUA PADA ANAK SEBAGAI SARANA IDENTIFIKASI ODONTOLOGI FORENSIK PADA ETNIS BANJAR - Muhammad Wafii Ramadhan; Bayu Indra Sukmana; Isyana Erlita; Irnamanda D.H.; Huldani Huldani (Dentin, 2024)
Background: Rugae palatine is a forensic organ that can survive and not be altered by any trauma such as from burns. Rugae palatina is one of the organs in the oral cavity that is unique in that there is no same pattern between individuals. This pattern also has peculiarities between individuals and gender. Palatine rugae can also be inherited from parents to children. Purpose: To analyze the inheritance of palatine rugae from parents to children in Banjar Ethnicity. Method: The method used in this research is analytic research with cross sectional method. This study was conducted on 32 families or 96 people whose number of students was divided into 16 men and 16 women. This study was conducted with photographic techniques using fullframe cameras and lenses, occlusal mirrors, LED lights. The results of photography are carried out in the editing stage in the photoshop application with the pentool feature. The data obtained and analyzed using the contingency coefficient correlation test. Results: The results showed a correlation in palatal rugae patterns. The father-offspring and mother-offspring contingency coefficient scores (0.708, 0.760) respectively which indicated a strong correlation in shape patterns between offspring and their parents. These correlations were statistically significant (p value ≤ 0.05). Conclusion: There is a strong and significant inheritance of palatine rugae between father and mother in children. Fathers and mothers have an equal chance of inheriting palatine rugae.Keywords : Banjar Tribe, Forensics, Inheritance, Palatine Rugae, Personal Identification.